Eco-friendly transparent poplar-based composites that are stable and flexible at high temperature. Issue 37 (11th July 2019) - Zou, Weihua; Sun, Delin; Wang, Zhangheng; Li, Ruoyao; Yu, Wenxuan; Zhang, Pingfang
Abstract : Farmed poplar could meet the human demand for transparent wood-based composites to replace glass, avoiding the consumption of natural forest resources. Abstract : Farmed poplar could meet the human demand for transparent wood-based composites to replace glass, avoiding the consumption of natural forest resources. We removed the lignin of poplar using a potassium hydroxide (KOH) and deionized water solution, the waste black liquor could be converted into compound potassium fertilizer after being neutralized by phosphoric acid. Polyurethane (PU) was then added to the lignin-stripped poplar and hardened, the transparent poplar-based composite (TPC) has stable transparency at high temperatures, and flexibility – it elongates (about 15%) before breaking. These properties could provide more uses in hot environments requiring a flexible shape. The TPC PU provides transmittance of 85%, haze of 83%, and anisotropic light diffraction.